Drawing Pattern On Novels In Contemporary Art - Jana, I Made; Sujana, I Wayan; Muka, I Ketut (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2019)
This study is prompted by the concern over stagnant rates of creation in producing contemporary statues in Bali, both in the northern and southern regions, by using stone, wood, and metal mediums. The technology of using gips (plaster of Paris) is easier in statue production, however dismisses innovation in the process. The researcher took interest in I Wayan Sujana’s 10 years long research (2007-2017) on transferring of the unconscious onto art from novels (books). Based on that research I Wayan Sujana produced thousands of drawings with rich periodicity patterns. Those patterns are reviewed and selected to be made as contemporary statues. The production method for the contemporary statues, using Drawing Pattern on Novel, was participatory, involving traditional art carving experts. User Participation Method, an approach with user involvement in the art, judgment and creation methods by SP Gustami, was employed to conduct this study. The data was gathered with interviews, observation, documentation, and then exploration, planning and embodiment. This study aimed to create innovation of the fine arts, based on research, using Drawing Pattern on Novels, and can be recognized as part of Indonesian fine arts development. Indonesian contemporary fine arts focuses on local genius as the spirit of its creation. This research generated innovative statutes from stone with Indonesian national culture’s aesthetic motifs.